2022
DOI: 10.3389/fimmu.2022.890263
|View full text |Cite
|
Sign up to set email alerts
|

The difference in CD4+ T cell immunity between high- and low-virulence Tembusu viruses is mainly related to residues 151 and 304 in the envelope protein

Abstract: Tembusu virus (TMUV) can result in a severe disease affecting domestic ducks. The role of T cells in protection from TMUV infection and the molecular basis of T cell-mediated protection against TMUV remain largely uncharacterized. Here, we used the high-virulence TMUV strain Y and the low-virulence TMUV strain PS to investigate the protective role for TMUV-specific CD4+ and CD8+ T cells. When tested in a 5-day-old Pekin duck model, Y and PS induced comparable levels of neutralizing antibody, whereas Y elicited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The difference in the pathogenicity and disease severity between these two clusters may be partly associated with the variation in inducing host immune responses, particularly cellular immune responses. A previous study showed that highly virulent DTMUV elicited stronger cellular immune response than low virulent DTMUV, whereas both of them induced comparable levels of neutralizing antibodies [14]. Additional studies are required to clarify the role of host immune responses on the pathogenicity and virulence differences between cluster 1 and 2.1 DTMUVs.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The difference in the pathogenicity and disease severity between these two clusters may be partly associated with the variation in inducing host immune responses, particularly cellular immune responses. A previous study showed that highly virulent DTMUV elicited stronger cellular immune response than low virulent DTMUV, whereas both of them induced comparable levels of neutralizing antibodies [14]. Additional studies are required to clarify the role of host immune responses on the pathogenicity and virulence differences between cluster 1 and 2.1 DTMUVs.…”
Section: Discussionmentioning
confidence: 97%
“…The viral strain/genotype is believed to be one of the most important factors affecting the virulence and pathogenicity of DTMUV [12][13][14]. Most of the DTMUV pathogenesis evaluation has mainly focused on cluster 2, while information on the pathogenesis of other DTMUV clusters, particularly cluster 1, is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation